Meningkatkan Kompetensi Guru dalam Menyambut Kurikulum Merdeka - Fitrina Susanti; Lidya Fitri; Asmendri Asmendri; Milya Sari (Lembaga Penelitian, Penerbitan dan Pengabdian (LP3M) IAI Al-Urwatul Wutsqo Jombang, 2024)
Education is a process of transforming knowledge from the teacher as an educator to his students as students. The teacher plays a very important role in improving the quality of the nation, a human being who has the character of karimah, in accordance with what was sparked by Nadhim Makarim in the independent learning curriculum that teachers must change, teachers must make changes in learning towards a better direction, learning in favor of students to achieve learning goals and create an environment learning that is conducive, comfortable, interesting and innovative, to welcome the independent learning curriculum teachers must continue to strive to develop their competencies, namely pedagogic competence, personal competence, social competence and professional competence. This study uses a descriptive qualitative approach with literature study methods and content analysis techniques to produce accurate data